Cultivating Creative Character Values and Love for Culture In Students Through Extra-Curricular Activities of Karawitan Arts at State Elementary School 2 Semedo, Pekuncen District - Danang Sulistyawan, Guntur; Ardy Wiyani, Novan (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Karawitan extracurricular activities can be used as a medium to instill creative character and love of culture in students. This study aims to describe how the implementation of karawitan art extracurricular activities at SD Negeri 2 Semedo in instilling creative character values ​​and love of culture in students. The location of this study is SD Negeri 2 Semedo. The subjects in this study were students of grades III-VI of SD Negeri 2 Semedo. The method used in this study is descriptive research with a qualitative approach. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques use the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of instilling creative character values ​​and love of culture in students through karawitan art extracurricular activities at SD Negeri 2 Semedo in its application is quite good. The presence of karawitan devices is very important because it helps the sustainability of karawitan learning at SD Negeri 2 Semedo. Learning applied in karawitan extracurricular activities provides more insight into the diversity of cultures in it and can stimulate the cognitive and intellectual development of students.